Using inertial measurement units originally developed for biomechanics for modal testing of civil engineering structures. (1st May 2018) - Hester, David; Brownjohn, James; Bocian, Mateusz; Xu, Yan; Quattrone, Antonino
Highlights: Inertial measurement units (IMUs) from biomechanics research are introduced. IMUs are compared to a conventional sensor (CS) network during modal tests on: A laboratory floor structure where the IMU's performed as well as the CS. A road bridge where IMU's and CS both identified the mode shapes correctly. An office tower where IMUs performed well but had some limitations with respect to CS. Abstract: This paper explores the use of wireless Inertial Measurement Units (IMU) originally developed for bio-mechanical research applications for modal testing of civil engineering infrastructure. Due to their biomechanics origin, these devices combine a triaxial accelerometer with gyroscopes and magnetometers for orientation, as well as on board data logging capability and wireless communication for optional data streaming and to coordinate synchronisation with other IMUs in a network. The motivation for application to civil structures is that their capabilities and simple operating procedures make them suitable for modal testing of many types of civil infrastructure of limited dimension including footbridges and floors while also enabling recovering of dynamic forces generated and applied to structures by moving humans. To explore their capabilities in civil applications, the IMUs are evaluated through modal tests on three different structures with increasing challenge of spatial and environmental complexity. These are, a full-scale floor mock-up in a laboratory, a short span road bridge and a seven story office tower. For each case, the results from the IMUs are compared with those from a conventional wired system to identify the limitations. The main conclusion is that the relatively high noise floor and limited communication range will not be a serious limitation in the great majority of typical civil modal test applications where convenient operation is a significant advantage over conventional wired systems.